The System Of Professional Training Of Future Teachers: Functional Approach - Ilyin, Aleksandr (2018)
The presence of a certain training of students, future teachers, is important for modern education. A complex social structure, formed by information technology actively, requires that the modern teacher ought to be fully prepared for various manifestations of sociality and broad outlook. A modern pedagogical university should form these characteristics of a specialist. Preparedness for the implementation of various functions and competences must be purposefully included in the training of future teachers. For this purpose, an important aim is to study the significance of the multifaceted functional approach in education. Functional analysis of the system of professional training of future teachers is an important preparatory stage in the implementation of the program for the comprehensive development of students-teachers.Among the many functions of the education system, we can distinguish the following ones: translational, axiological, activity, educational, educational and developing functions. The most important of them is the axiological, activity and developing functions. The axiological function forms the world of values and it is very important that these values are to be directed to the solution of human-forming, humanistic tasks. The activity function allows the future specialist to realize his tasks, despite the difficulties that arise. The development task of education will make it possible to develop the ability to complete the course of work.